Pendampingan Bimbingan Belajar Anak Usia Sekolah Dasar di Rumah CALISTUNG Kereng Bangkirai Kota Palangka Raya - Ahmad Rasid Ambrullah; Anisa Anisa; Aswa Wardana; Ilham Dwi Saputro; Sri Nuryana Sari (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
The issue in the realm of education today is after the corona virus pandemic which expects the government to take steps forward in defeating the spread of the corona virus in the field of education. The government implements the implementation of home learning programs through online-based classes or commonly referred to as online. However, now that the corona virus pandemic is starting to subside, the government concludes that teaching and learning activities can be carried out directly which is generally called the implementation of offline learning. This study aims to determine the effect of tutoring at RUMAH CALISTUNG on the learning outcomes of fourth grade students at SD Negeri 2 Kereng Bangkirai, Palangka Raya City. This research is a quantitative research. The sample used in this study were 30 fourth grade students of SD Negeri 2 Kereng Bangkirai, Palangka Raya City. This study uses a method consisting of observation, documentation and tests. The results of this study indicate that there is an effect of tutoring on student learning outcomes, this is proven by the results of the first cycle only 40% of the 70% target is completed. This shows that only 12 students have completed out of 30 students in the learning evaluation. After making improvements and adjustments to the implementation of extra learning outside of school hours in the second cycle, there was an increase to 96.7% which was completed. This shows that from 30 students only 1 student has not completed the evaluation of learning outcomes. It can be concluded that tutoring at CALIStung House can be a program to further develop student learning outcomes